RANCANG BANGUN BANTAL TERAPI BERBASIS ARDUINO - Ningtias, Diah Rahayu; Sudarma, Made Putra; Harsoyo, Imam Tri (Universitas Semarang, 2019)
One form of physiotherapy is utilizing heat for recovery. Heat therapy can open blood vessels wider, thereby increasing blood flow and supply of oxygen and nutrients to reduce pain in joints, muscles, ligaments and injured tanks. To help health services in the field of physiotherapy the author modifies the therapeutic pillow with Arduino Uno and DS18B20 based as a temperature sensor, LCD as a temperature viewer and a timer and button that functions to choose how long it takes to do therapy. The design of therapeutic pillows is divided into two, namely hardware and software design, hardware design including power supply, a series of drivers and system scenarios. While the software design of this tool uses the Arduino and proteus applications as software. The result of the percentage error at the TP2 measurement is 0.02%. The measurement results on TP3 when the tool is off or off, then the circuit does not get a voltage while when the device is turned on or on the driver circuit gets a voltage of 1.4 Volt. After making the process of making, testing, testing tools and data collection, the author has succeeded in designing a heat therapy pillow using a temperature sensor and ARDUINO UNO based timer controller that can provide convenience when going to heat therapy because it is equipped with an automatically controlled temperature sensor and controller timer. by DS1820 temperature sensor. A therapeutic pillow based on Arduino with 10 minutes of therapy results in a temperature of 41 °C.